THE POETICS OF JUAN GONZALO ROSE: RHETORICAL ANALYSIS OF "RETURN-CIRCLE" AND "CONVALESCENCE" - Álvarez Rosales, Anderson Josué (2019)
Although he has not achieved the international fame of other authors, Juan Gonzalo Rose (1928-1983) is considered one of the most important writers of Peruvian letters because of the sensitivity he develops in his work and the varied themes he presents. In this sense, in the present work we propose to perform a critical review of the work of Juan Gonzalo Rose and the rhetorical analysis of two of his poems: "Return-circle" and "Convalescence".